Writing Facts Interdisciplinary Discussions of a Key Concept in Modernity - Knaller, Susanne (Lettre, 2023)
»Fact« is one of the most crucial inventions of modern times. Susanne Knaller discusses the functions of this powerful notion in the arts and the sciences, its impact on aesthetic models and systems of knowledge. The practice of writing provides an effective procedure to realize and to understand facts. This concerns preparatory procedures, formal choices, models of argumentation, and narrative patterns. By considering »writing facts« and »writing facts«, the volume shows why and how »facts« are a result of knowledge, rules, and norms as well as of description, argumentation, and narration. This approach allows new perspectives on »fact« and its impact on modernity.